(untitled) (Journal of Fiber Bioengineering and Informatics, 2016)
In the paper, two kinds of Woven Heated Fabrics (WHFs) were prepared and evaluated. WHFs were fabricated by integrated silver filaments into fabrics with the same interval distance, and silver paste was coated on the crossing points of some WHFs to decrease contact resistance. Subsequently, surface infrared temperature images and temperature simulated by finite element method were utilized to evaluate the performance of WHFs. Experimental results showed surface temperature of WHFs is non-linear correlation with time when voltage was loaded on two ends of WHFs, but the surface equilibrium temperature of WHFs is linear correlation with loaded voltage and power consumption. However, simulated surface temperature is highly consistent with the measured surface temperature of silver filaments by adjusting the Heat Transfer Convection Coefficient (HTCC) at different loaded voltage. WHFs have wide application prospect in Electric Heating Garment (EHG) in the future. Infrared temperature images and finite element simulation can decrease the cost and enhance design efficiency of WHFs.